Responsabilidade social empresarial: o caso Deloitte - Pombal, Lúcia Cristina Azevedo (2010)
Recently, the Corporate Social Responsibility issue has been presented to the society as a significativily relevant, polemic and dynamic subject. Although studies show that companies have an approach about this theme which involves a socially responsible actions management with their stakeholders, few companies implement this market tool in their business by unknowing its results. This paper aims to fill in this gap by examining the practices and concepts involved in this issue. The study, thus, seeks to identify the level of the Internal Social Responsibility in an organization, based on the experience of the audit and consultant company, Deloitte Touche Tohmatsu, focused on Corporate Consulting at Rio de Janeiro. Concepts about community organization, company responsibilities and social role, sustainable development and the Corporate Social Responsibility were taken as the theory basis. The paper presents a qualitative approach and the means employed were literature and the work field. The research was done with 41 consultants, of which 37 answered the questionnaire. As a result, the research points to confirm the assumptions raised, which means, the Corporate Social Responsibility can be used as a management model able to focus its business on the sustainable development, stakeholders and society commitment.